Technical advantages bridging the preservation limits of painted decoration of Neolithic ceramic figurines - Ludmila Kaňáková; Vojtěch Nosek; Attila Kreiter; László Előd Aradi; Martin Košťál (Virtual Archaeology Review, 2025)
Painting on ceramic objects is one of the most outstanding features of visual narration of the Neolithic material culture in Southeastern and partly in Central Europe. Unfortunately, post-firing painting is usually poorly preserved due to deposition conditions. Moreover, it may have been damaged or contaminated during post-excavation and conservation processes in the past. This project studies how new methods of pigment traces visual detection bring about a more successful identification of pigment traces and reconstruction of motifs; this leads to both more targeted protection without contaminants and a broader understanding of the motifs preferred by Neolithic societies in their narrative expression. Decorrelation algorithms have been widely used to analyse rock art and wall paintings, but their application to fragile pigments on mobile artefacts remains limited. DStretch, a key tool in this process, enhances colour contrasts in digital images to detect faint pigment traces, which are often overlooked in standard macroscopic analysis. By applying DStretch to high-resolution photographs or 3D model textures, pigment residues can be identified without damaging the object. The algorithm’s versatility extends to different colour channels, making it possible to detect subtle traces across different pigments, improving overall data preservation and analysis. 378 fragments of Neolithic ceramic figurines from the Lengyel culture site Těšetice-Kyjovice – Sutny, the largest known collection in central Europe, have been studied. The DStretch results were verified using reflected-light microscopy, and samples of the most commonly used pigments were analysed by Raman spectroscopy. In the past, painting the figurines was considered a minor practice, which led to believe that only 25 % of them were painted. Thanks to the methods applied in this project, it is revealed that, despite the intensive removal of pigments during post-excavation surface cleaning, almost 60 % of figurines were painted. New data on the structure and origin of pigments were collected as well as data concerning the nature of the motifs.